Distribution System for Urban Agricultural Products Using Genetic Algorithms based on Android - Uzzin Nadhori, Isbat; Syauqi Ahsan, Ahmad; Astika Saputra, Ferry; Hendra Prasetya, Tony (International Journal of Engineering and Technology, 2018)
Urban agriculture is an agricultural activity (farming and cultivation) inside the city. Urban agriculture generally produces fruits and vegetables that have a short shelf life. Urban agricultural activities include production, distribution and marketing of agricultural products. Efficient distribution's routes are highly needed for better delivery of agricultural products to customers. Failure in route selection could increase shipping and operating costs, and also could reduce the product's quality. Itt is necessary to obtain the right route to distribute products that could reduce operational costs and maintain the quality of product until the destination. This research develops an application to determine the distribution route for urban agricultural products using genetic algorithms. This application can calculate the optimal distribution route so that in the process of distribution of urban agricultural products can be done accurately and efficiently. Route optimization with genetic algorithms successfully optimizes the best route, and can be seen from the fitness value that continues to increase each generationÂ